Editorial: identifying candidates for pegylated interferon add‐on to entecavir therapy in patients with HBeAg‐positive chronic hepatitis B – authors' reply. Issue 5 (11th February 2019) - Liem, Kin Seng; Janssen, Harry L. A.
Abstract : Linked Content This article is linked to Liem et al and Peng papers. To view these articles, visit https://doi.org/10.1111/apt.15098 and https://doi.org/10.1111/apt.15136 .